Determining Scholarship Recipients at STIT Prabumulih Using the AHP Method - Christian, Andi; Ariansyah, Ariansyah; Wahyuni, Anggie Sri (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2023)
In every educational institution, especially universities, there are lots of scholarships offered to students. Likewise with the Prabumulih College of Engineering (STIT Prabumulih) which has a scholarship program for its students by applying predetermined rules or criteria, for example, parents' income, parents' dependents, student achievement index scores, etc. Due to this, not all scholarship recipients who apply for scholarships will receive a scholarship. The problem faced by the campus today is in the process of winning scholarships. therefore a decision support system is needed that can assist in providing scholarship recipient recommendations. In this study the authors used the AHP method and the Expert Choice application. From the calculation results obtained by the specified criteria, the GPA of 0.389 is the highest priority weight compared to other criteria. Then, from the results of calculating student data or all alternatives, the total value of each student is obtained. It can be concluded that the one who can be recommended to get a UKT scholarship is Student A because it has the highest score, namely 16.6% of the total calculated.